2022
DOI: 10.1039/d1nr07995f
|View full text |Cite
|
Sign up to set email alerts
|

Assembly mechanism of surface-functionalized nanocubes

Abstract: Faceted nanoparticles can be used as building blocks to assemble nanomaterials with exceptional optical and catalytic properties. Recent studies have shown that surface functionalization of such nanoparticles with organic molecules,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…En presencia de agentes químicos (surfactantes), las propiedades superficiales e interfaciales pueden verse modificadas. La fuerza de gravedad no aplica como en macropartículas, ya que esta resulta despreciable frente a fuerzas viscosas o intermoleculares; en cuanto a las interacciones partículapartícula están dominadas por fuerzas débiles de Van der Waals, interacciones polares y electrostáticas más fuertes o interacciones covalentes (Boggiano et al, 2021;Hyun-jong & Arya, 2020;Zambrano, 2020).…”
Section: El Problema Alcanza Las Escalas Más Pequeñas En Tamaño Pero ...unclassified
“…En presencia de agentes químicos (surfactantes), las propiedades superficiales e interfaciales pueden verse modificadas. La fuerza de gravedad no aplica como en macropartículas, ya que esta resulta despreciable frente a fuerzas viscosas o intermoleculares; en cuanto a las interacciones partículapartícula están dominadas por fuerzas débiles de Van der Waals, interacciones polares y electrostáticas más fuertes o interacciones covalentes (Boggiano et al, 2021;Hyun-jong & Arya, 2020;Zambrano, 2020).…”
Section: El Problema Alcanza Las Escalas Más Pequeñas En Tamaño Pero ...unclassified
“…For example, Monte Carlo (MC) simulations of polymer-grafted nanocubes were performed to investigate the assembly mechanism in detail, and it was found that the free energy barriers between metastable states depend on the interaction strength and surface roughness of the nanocubes and steric repulsion from the grafts. 47,48 In addition, we recently investigated the equilibrium self-assembly of amphiphilic cubes and the assembly dynamics under shear using a combination of molecular dynamics (MD) and kinetic MC simulations. 49,50 Previous studies have focused on the self-assembly behavior induced by the design of nanocubes, but have not investigated the relationship between complex self-assembled structures and the resulting macroscopic properties owing to the computational complexity multiscale problems involve.…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge gap in fundamental understanding of how ligand-mediated interactions propagate to macroscopic behaviors makes it hard to decouple the role of the ligand shell versus nanoparticle core in driving self-assembly. While there have been computational efforts developed to tackle this key question, [21][22][23] they are often limited in system size due to the need to simulate the entire ligand shell coating the nanoparticle core and therefore cannot predict, a priori, the emergent self-assembly superlattices. Conversely, thermodynamic perturbation theory based approaches have been successfully employed to design co-assemblies of ligand-functionalized anisotropic nanoparticles, 12,13,15 but these efforts focus on free energy-based phase predictions and do not provide an explanation regarding how ligand-ligand interactions propagate across multiple length scales.…”
Section: Introductionmentioning
confidence: 99%